An overview of the biological disease modifying drugs available for arthritic conditions in South Africa - Leonie Harmse (AOSIS, 2016)
The past decade has seen a major change in the treatment options and strategies for rheumatoid arthritis (RA) and the other immune-mediated arthritic diseases. The disease modifying antirheumatic drugs (DMARDs) are now used in early stages of the disease in order to preserve joint architecture. There are two groups of DMARDs, the small molecules, like methotrexate, and the biological DMARDs, which are frequently referred to as “magic bullets” since they target specific cytokines and immune cells associated with arthritic conditions. They are monoclonal antibodies or fusion proteins designed to bind and inactivate immune targets.